2022
DOI: 10.1111/gcb.16383
|View full text |Cite
|
Sign up to set email alerts
|

Soil disturbance and invasion magnify CO2 effects on grassland productivity, reducing diversity

Abstract: Climate change, disturbance, and plant invasion threaten grassland ecosystems, but their combined and interactive effects are poorly understood. Here, we examine how the combination of disturbance and plant invasion influences the sensitivity of mixedgrass prairie to elevated carbon dioxide (eCO2) and warming. We established subplots of intact prairie and disturbed/invaded prairie within a free-air CO2 enrichment (to 600 ppmv) by infrared warming (+1.5 °C day, 3 °C night) experiment and followed plant and soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The RRSRU scientists found that elevated CO 2 greatly increased diffuse knapweed ( Centaurea diffusa Lam.) biomass in disturbed mixed-grass prairie, leading to corresponding decreases in plant diversity (Blumenthal et al 2022). In western rangeland, B. tectorum can reduce fire return times from decades to less than 5 yr, with concomitant decreases in ecosystem diversity and the establishment of B. tectorum monocultures (Fusco et al 2019).…”
Section: Present—ars Weed Science Researchmentioning
confidence: 99%
“…The RRSRU scientists found that elevated CO 2 greatly increased diffuse knapweed ( Centaurea diffusa Lam.) biomass in disturbed mixed-grass prairie, leading to corresponding decreases in plant diversity (Blumenthal et al 2022). In western rangeland, B. tectorum can reduce fire return times from decades to less than 5 yr, with concomitant decreases in ecosystem diversity and the establishment of B. tectorum monocultures (Fusco et al 2019).…”
Section: Present—ars Weed Science Researchmentioning
confidence: 99%
“…Human activities such as agricultural production and fossil fuel combustion add ~200 Tg/year of nitrogen (N) to global ecosystems, approximately equal to that provided by natural N fixation [ 1 ]. Land use changes, climate changes, and N deposition increase are the major causes of biodiversity loss [ 2 , 3 ]. Numerous studies showed that plant functional traits and ecosystem functions changed significantly under N deposition increase and biodiversity loss [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%